Hodnocení výkonnosti vybraného podniku podle modelu Start Plus - Studený, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá problematikou hodnocení výkonnosti vybrané společnosti pomocí vícekriteriálního modelu START PLUS. Na základě vyhodnocení jednotlivých oblastí je sestaveno bodové ohodnocení, jsou identifikovány silné stránky společnosti a oblasti pro zlepšení. V závěru práce jsou navržena opatření, díky kterým by bylo možné dosáhnout zvýšení výkonnosti analyzované společnosti.

The master thesis deals with the performance evaluation of the selected company according to the multi-criteria model START PLUS. Based on the assessment of key performance indicators in individual areas a scoring is created in order to identify strengths and areas for improvement. The last chapter of this thesis is dedicated to proposal of concrete measures and recommendations to increase the performance of the analyzed company.
Performance Assessment of the Selected Company according to the Model Start Plus
Keywords: START PLUS; EFQM; výkonnost; management kvality; ISO; měření výkonnosti; hodnocení; START PLUS; EFQM; performance; quality management; ISO; performance measurement; assessment